IPhone and iPad apps for absolute beginners - Lewis, Rory (Apress : Distributed to the Book trade worldwide by Springer-Verlag New York, 2010)
Provides information on building applications for the iPhone and the iPad, covering such topics as code, multiple graphics, table views, arrays, MapKit.